MELDIGANSI (Media Pembelajaran Digital Akuntansi) Berbasis Android Bagi Siswa SMA - Efni S.Pd. Cerya; Zul Afdal; Joni Susilowibowo (Universitas Negeri Padang, 2021)
An accounting lesson is a lesson that requires students to be able to understand the concept of theory and calculation simultaneously. In order for learning to be interesting, varied, and interactive, learning media is needed for students so that they will be interested in participating in the learning process. Android-based digital learning media can help students understand learning both online and offline. The types of research use Research and Development (R&D). The test of the validity of the Android-based learning media is carried out by competent validators consisting of material expert validators, linguists, and media experts. The development of digital accounting learning media was developed using a 4-D model, define, designed, develop and disseminate. However, this research is limited to the dissemination stage. The results of this study indicate that the development of accounting digital learning media is declared